Using Spent Used Cooking Oil As An Aromatic Lamp - Marnida Yusfiani; Moondra Zubir; Ani Sutiani; Cynthia Crasela Siregar; Gita Dwi Ayu Ninzy Tampubolon; Vindy Yosensi Saragih; Caecilia Antonia Purba; Najwa Shauqiyah (Universitas Negeri Medan, 2025)
The Carnot cycle consists of four processes: two isothermal and two adiabatic, which increase efficiency by regulating temperature. In contrast, the Rankine cycle overcomes Carnot's weaknesses by using steam heating and condensation. In addition, making candles from used cooking oil is an environmentally friendly innovation that processes waste into useful products. This process involves heating the oil to remove odors, mixing it with paraffin, and adding aromas. Making lamps from cans also utilizes used materials, demonstrating creativity in waste management. The 1:3 ratio (paraffin:oil), which is more oil-dominant, results in the fastest and most efficient burn, with the highest amount of candle mass burned after 40 minutes. This is suitable for applications that require rapid burning, such as in the creation of a moving nightlight that utilizes the Carnot cycle to convert heat into mechanical energy for movement. In contrast, the 3:1 ratio (paraffin:oil) produces a harder and more durable candle, with less mass burned, making it more suitable for long-term use and stable movement. The 1:2 and 2:1 ratios provide a balance between burn duration and light intensity, allowing them to be chosen based on specific needs.